2019
DOI: 10.1111/ecca.12304
|View full text |Cite
|
Sign up to set email alerts
|

Who Got the Brexit Blues? The Effect of Brexit on Subjective Wellbeing in the UK

Abstract: We use the 2015–16 waves of the UK Household Longitudinal Study (Understanding Society) to look at subjective wellbeing around the time of the June 2016 EU membership Referendum in the UK (Brexit). We employ measures of both evaluative and affective wellbeing, namely life satisfaction and mental distress, respectively. We find that those reporting lower life satisfaction in 2015 were more likely to express a preference for leaving the EU in 2016, while mental distress was less predictive of pro‐Brexit attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 23 publications
2
56
3
Order By: Relevance
“…There is little published evidence to date regarding the potentially harmful psychological impact of the Brexit era, although one examination of the UK Household Longitudinal Study ('Understanding Society') reported a rise in average levels of psychological distress following the referendum, with no apparent difference in patterns of association observed between people who voted to 'Leave' versus those who voted to 'Remain'. 31 The study's authors concluded that levels of subjective well-being may have been both a cause and consequence of the slender national majority vote in favour of Brexit in 2016. These findings, as well as the disquieting correlations that our investigation has revealed, indicate a need for investigation of the psychological sequelae of the societal divisions and insecurities that have arisen before, during and following the 2016 national referendum.…”
Section: Discussionmentioning
confidence: 99%
“…There is little published evidence to date regarding the potentially harmful psychological impact of the Brexit era, although one examination of the UK Household Longitudinal Study ('Understanding Society') reported a rise in average levels of psychological distress following the referendum, with no apparent difference in patterns of association observed between people who voted to 'Leave' versus those who voted to 'Remain'. 31 The study's authors concluded that levels of subjective well-being may have been both a cause and consequence of the slender national majority vote in favour of Brexit in 2016. These findings, as well as the disquieting correlations that our investigation has revealed, indicate a need for investigation of the psychological sequelae of the societal divisions and insecurities that have arisen before, during and following the 2016 national referendum.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach, using a difference-in-differences econometric model with previous years as a control group, has been followed in previous studies in the absence of a control group involving a different population. 5,[26][27] The difference-in-differences econometric model is presented in Equation 1:…”
Section: Methodsmentioning
confidence: 99%
“…The UKHLS and its predecessor contain a rich set of subjective well-being measures and are widely used to study the determinants of well-being (see, for example, Clark (2019), Powdthavee et al (2019), Binder and Coad (2015) and Clark and Georgellis (2013)). Here, we focus on three key measures: job satisfaction, satisfaction with life overall, and mental distress as captured by the 12-item General Health Questionnaire (GHQ).…”
Section: Outcomes Of Interestmentioning
confidence: 99%